ACADEMIC ENGLISH PROFICIENCY: TOEFL ITP COMPARISON BETWEEN UNDERGRADUATES AND GRADUATES AT AN ISLAMIC UNIVERSITY - Wim Banu Ukhrowi; Binti Qani’ah (Al-Irsyad: Journal of Education Science, 2025)
This research explores the gap in academic English proficiency between undergraduate (S1) and postgraduate (S2) students at a pesantren-based university, using TOEFL ITP scores as the primary benchmark. Although academic English has been widely studied in university contexts, limited attention has been given to pesantren-based institutions—especially in comparing the proficiency levels of students across educational stages. This study addresses that gap by offering fresh insights from a unique educational setting that combines religious and academic curricula. A quantitative comparative approach applied involved 140 students, divided equally between the undergraduate and postgraduate levels. After testing the data distribution using the Shapiro-Wilk test, results indicated non-normality (p < 0.05), leading to the use of the Mann-Whitney U test for statistical comparison. Descriptive analysis revealed that postgraduate students scored higher on average (M = 468.9; SD = 23.57) than undergraduates (M = 447.6; SD = 20.32). Furthermore, score ranges differed noticeably: undergraduates commonly scored between 430–460, while postgraduates were more frequently in the 460–500 range. The Mann-Whitney U test confirmed a statistically significant difference between the two groups (U = 1890.500, p = 0.020). These findings suggest a clear disparity in academic English mastery between undergraduate and postgraduate students in this context. The results highlight the importance of implementing targeted academic interventions at the undergraduate level—such as integrated English instruction, intensive support programs, and context-based language learning. By reinforcing English proficiency early in students' academic journeys, it can prepare their graduates to succeed in global academic and professional arenas.